Agro Techno Park Accounting 5.0: Integrated Farming Accounting Technology BUMDes Suci untuk Ketahanan Pangan Berkelanjutan - Sugeng Hartanto; Endro Sugiartono; Luluk Cahyo Wiyono; Arisona Ahmad; Galih Dwi Premasanam (Jurnal Pendidikan Akuntansi (JPAK), 2025)
This study discusses the fragmentation of management in the agriculture, livestock, and fisheries sectors in BUMDes, which has the potential to cause cost inefficiencies and lack of productivity. This study presents an integrated financial management model for BUMDes across sectors. The research method uses a qualitative approach, with data obtained through interviews, observation, and documentation. This research began with an analysis of the problems faced by BUMDes Suci in managing its business units. It also examined how Agro Techno Park Accounting 5.0 could be applied to produce an integrated accounting model that supports its financial management. The advantages of the integrated farming model are cost efficiency in production, optimization of local resources, increased productivity, and the potential for developing agro-based educational tourism.